Optimizing Early Childhood Cognitive Development through Parental Stimulation - Zain, Nabilah Kamiliyah; Iswinarti, Iswinarti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This research highlights the importance of parental caregiving in the cognitive development of children during early childhood, a period of rapid brain growth. Interaction with parents and a stimulating home environment significantly influence this development. Many parents lack understanding of effective ways to support their child's cognitive development, necessitating interventions that help enhance cognitive stimulation at home. This study reviews the literature to illustrate the effectiveness of positive parental stimulation in promoting early childhood cognitive development. The findings indicate that parental stimulation, such as a supportive home environment and positive interactions, is crucial for early cognitive development. Interventions that improve parenting practices are effective in enhancing children's cognitive abilities. A lack of stimulation can hinder a child's development, making supportive parenting programs essential. Home stimulation, positive interactions, and authoritative parenting styles are key to optimal cognitive development in children.Penelitian ini menyoroti pentingnya pengasuhan orang tua dalam perkembangan kognitif anak pada masa awal, saat otak berkembang pesat. Interaksi dengan orang tua dan lingkungan rumah yang stimulatif sangat memengaruhi perkembangan ini. Banyak orang tua kurang memahami cara efektif untuk mendukung perkembangan kognitif anak, sehingga diperlukan intervensi yang membantu meningkatkan stimulasi kognitif di rumah. Studi ini meninjau literatur untuk menggambarkan efektivitas stimulasi positif oleh orang tua dalam meningkatkan perkembangan kognitif anak usia dini. Hasil dari penelitian ini menunjukkan bahwa stimulasi orang tua, seperti lingkungan rumah yang mendukung dan interaksi positif, sangat penting untuk perkembangan kognitif anak usia dini. Intervensi yang meningkatkan praktik pengasuhan efektif dalam meningkatkan kemampuan kognitif anak. Kekurangan stimulasi dapat menghambat perkembangan anak, sehingga program pengasuhan yang mendukung sangat diperlukan. Stimulasi rumah, interaksi positif, dan gaya pengasuhan otoritatif adalah kunci untuk perkembangan kognitif anak yang optimal.